Odgers$1 (BAustralian Senate Practices - Harry Evans. (ed) (Canberra : Dept. of the Senate, 2008., 1999)
The Senate and its Constitutional Role, the Senate, bicameralism and federalism, Bases of the two Houses, Rationale of Bicameralism